2006
DOI: 10.1063/1.2221690
|View full text |Cite
|
Sign up to set email alerts
|

Chemical diffusion of CO in mixed CO+O adlayers and reaction-front propagation in CO oxidation on Pd(100)

Abstract: Within the framework of a realistic atomistic lattice-gas model, we present the theoretical formulation and simulation procedures for precise analysis of the chemical diffusion flux of highly mobile CO within a nonuniform interacting mixed CO+O adlayer on a Pd(100) surface. The approach applies in both regimes of relatively immobile unequilibrated and fairly mobile near-equilibrated O adlayer distributions. Spatiotemporal behavior in surface reactions is controlled by chemical diffusion in mixed adlayers. Thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…Mousa et al [8] investigated the catalytic CO oxidation on PdCu(110) single crystal alloy surfaces, and detected the regions of bistability by mass spectrometric reaction rate measurements. Liu and Evans [9] provided results for the steady-state bifurcation behavior for the catalytic oxidation of CO on single-crystal Pd(100) surfaces under ultrahigh vacuum (UHV) conditions. Pavlenko et al [10] showed that the diffusion of adsorbed CO between two Pt facets in catalytic CO oxidation leads to the appearance of complex multistability.…”
Section: Background and Previous Workmentioning
confidence: 99%
“…Mousa et al [8] investigated the catalytic CO oxidation on PdCu(110) single crystal alloy surfaces, and detected the regions of bistability by mass spectrometric reaction rate measurements. Liu and Evans [9] provided results for the steady-state bifurcation behavior for the catalytic oxidation of CO on single-crystal Pd(100) surfaces under ultrahigh vacuum (UHV) conditions. Pavlenko et al [10] showed that the diffusion of adsorbed CO between two Pt facets in catalytic CO oxidation leads to the appearance of complex multistability.…”
Section: Background and Previous Workmentioning
confidence: 99%
“…In general, we are interested in finite concentrations, in which case one must consider a many-particle version of the above percolative diffusion problem. 72,228…”
Section: → − ∇mentioning
confidence: 99%
“…The diffusion flux is given precisely by J CO = −Λ CO ∇μ CO , where the conductivity, Λ CO = Λ CO (θ CO ,{O}), also depends nontrivially on θ CO and {O}. 7,72,228 Other components of the conductivity tensor are negligible. Often O mobility is sufficiently high that the adlayer is fully locally equilibrated, and then all these quantities are fully…”
Section: General Theory and Analysis For Realistic Mslg Modelsmentioning
confidence: 99%
“…Such an asymmetric combination is not expected to correctly describe the spatiotemporal behavior of crowded systems, since Fickian diffusion does not respect the conservation laws imposed by the medium constraints. Some recent investigations [8,22], including this work, show that transport can be strongly affected by crowding effects as well. It would thus be interesting to analyze how the conclusions drawn in the limit of ideal diffusion are affected by nonideal contributions.…”
Section: Discussionmentioning
confidence: 54%
“…Notice the presence of cross-diffusive terms in the righthand side of Eqs. (21) and (22). Because of the balance (7), the effective chemical potential for the X species [μ X − μ * ] depends on the concentration of Y , and vice versa for Y .…”
Section: B Mass Transportmentioning
confidence: 99%